1988
DOI: 10.1210/endo-123-6-2736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on CRF Releasein Vitro*

Abstract: Acute ethanol exposure produces activation of the brain-pituitary-adrenal (BPA) axis, resulting in the release of ACTH, beta-endorphin, and glucocorticoids. While elevated levels of plasma glucocorticoids are also found after chronic ethanol administration, plasma ACTH and beta-endorphin are normal or reduced. It is also unclear whether chronic ethanol exposure results in tolerance to the stimulatory effect of ethanol on BPA activity. To determine the site and mechanism of ethanol action on the BPA axis we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…These findings suggest that alcohol may directly activate HPA axis through regulating the PVN cellular activity. Indeed, in vitro application of alcohol to hypothalamic tissue or primary hypothalamic cells induces the release of CRF (Redei et al, 1988; Li et al, 2005). In addition, CRF heteronuclear RNA quickly elevates within 20 min after in vivo alcohol administration in rats (Rivier and Lee, 1996; Ogilvie et al, 1998).…”
Section: Alcohol Stimulates the Release Of Stress Hormonesmentioning
confidence: 99%
“…These findings suggest that alcohol may directly activate HPA axis through regulating the PVN cellular activity. Indeed, in vitro application of alcohol to hypothalamic tissue or primary hypothalamic cells induces the release of CRF (Redei et al, 1988; Li et al, 2005). In addition, CRF heteronuclear RNA quickly elevates within 20 min after in vivo alcohol administration in rats (Rivier and Lee, 1996; Ogilvie et al, 1998).…”
Section: Alcohol Stimulates the Release Of Stress Hormonesmentioning
confidence: 99%
“…Acute ethanol administration is accompanied by increases in levels of CRF [18] and CRF-like immunoreactivity (CRF-IR) [19], as well as increased levels of CRF heteronuclear RNA (hnRNA) and messenger RNA (mRNA) [18, 20, 21] in the hypothalamus. Acute ethanol administration also induces activation of Ucn-positive cells in the perioculomotor urocortin-containing population of neurons (pIIIu, also known as the Edinger-Westphal nucleus) [22].…”
Section: The Effects Of Ethanol On the Crf/ucn Systemmentioning
confidence: 99%
“…In addition to its centrally mediated hypothermic effects, EtOH exposure activates the hypothalamic-pituitary-adrenal (HPA) axis (Redei et al, 1986(Redei et al, , 1988Rivier and Lee, 1996). Studies have also shown that alcohol generally suppresses the hypothalamic-pituitary-gonadotropin axes of animals and humans (Cicero and Badger, 1977;Mendelson et al, 1977;Rivier, 1999).…”
Section: Discussionmentioning
confidence: 99%